Collaboration and tension between institutions and units providing data management support. Issue 6 (10th April 2015) - Wright, Stephanie; Whitmire, Amanda; Zilinski, Lisa; Minor, David
Abstract : EDITOR'S SUMMARY A panel of speakers from three universities explored their challenges and progress in building programs to support research data management, whether within the library system or with research offices or computing groups. Since 2012 Oregon State University has partnered with its research office and graduate school, helping students prepare data for preservation and sharing and developing a graduate course for credit in research data management. Based on needs identified through an environmental scan, the University of Washington hired a data services coordinator to promote the services provided and to increase collaborations, visibility and support. Purdue University pairs data services specialists with subject liaison librarians to reach disciplinary faculty and researchers. The connections identify champions, lead to successful collaborations and, most importantly, provide the opportunity to show data services specialists as peers and collaborators. With basic services established, each institution looks forward to strengthening relationships and expanding services, skills and staffing.